2017
DOI: 10.1002/stem.2691
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt5a Receptor, Receptor Tyrosine Kinase-Like Orphan Receptor 2, Is a Predictive Cell Surface Marker of Human Mesenchymal Stem Cells with an Enhanced Capacity for Chondrogenic Differentiation

Abstract: Multipotent mesenchymal stem cells (MSCs) have enormous potential in tissue engineering and regenerative medicine. However, until now, their development for clinical use has been severely limited as they are a mixed population of cells with varying capacities for lineage differentiation and tissue formation. Here, we identify receptor tyrosine kinase‐like orphan receptor 2 (ROR2) as a cell surface marker expressed by those MSCs with an enhanced capacity for cartilage formation. We generated clonal human MSC po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 51 publications
1
62
1
Order By: Relevance
“…For example, pericytes expressing the Wnt receptor ROR2 demonstrate enhanced potential to undergo cartilage formation. 31 In another example, human pericytes can be distinguished based on aldehyde dehydrogenase expression into more "primitive" and more "differentiated" cell types. 15 Here, PDGFRα marks distinct perivascular osteoprogenitor cell subpopulations within AT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pericytes expressing the Wnt receptor ROR2 demonstrate enhanced potential to undergo cartilage formation. 31 In another example, human pericytes can be distinguished based on aldehyde dehydrogenase expression into more "primitive" and more "differentiated" cell types. 15 Here, PDGFRα marks distinct perivascular osteoprogenitor cell subpopulations within AT.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding bone formation, we have recently identified novel surface markers which typify PSC subsets endowed with higher osteogenic potential (Ding, Meyers et al, unpublished results), as was already recently done for pro-fibrotic ability [10] and chondrogenic capacity [56]. Ongoing studies will converge to explain the bone healing effect of pericytes and other regenerative perivascular cells, both natively in situ and following purification and transplantation, and contribute to the development of a refined therapeutic product (Table 3.1).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently confirmed that ALDH hi perivascular progenitors are developmentally more primitive than their ALDH lo counterparts (Hardy et al, 2017;Gomez-Salazar et al, in preparation). Perivascular cells and derived MSCs with superior chondrogenic potential have been identified by marker expression (Dickinson et al, 2017) and proximity to the joint (Hindle et al, 2016), while the subset of perivascular adventitial cells that express CD10 is considerably enriched in osteogenic progenitors, at the expense of adipogenic cells (Ding et al, 2019).…”
Section: Native Perivascular Progenitor Cells and Derived Mscs Are Anmentioning
confidence: 99%